Strengthening Financial Reporting Capacity in Village-Owned Enterprises: A Phased Participatory Mentoring Model for SAK EMKM Adoption in Samosir Regency, North Sumatra - Merry Anna Napitupulu; Duma Megaria Elisabeth; Dimita H. P. Purba; Septony B. Siahaan; Dompak Pasaribu; Rahel Junita; Rimky M. P. Simanjuntak; Tri Dharma Sipayung; Wesly A. Simanjuntak; Mulatua P. Silalahi; Rike Y. Panjaitan; Thomas Sumarsan Goh (Universitas Methodist Indonesia, 2026)
Village-Owned Enterprises (BUMDes) constitute a cornerstone of Indonesia’s rural economic development strategy, yet inadequate financial reporting capacity among their managers continues to erode organizational accountability and governance credibility. This community service activity tackled that challenge through a three-phase participatory mentoring program involving 25 BUMDes managers from three villages in Samosir Regency, North Sumatra namely BUMDes Marsada Tahi, BUMDes Hutanamora, and BUMDes Saoloan. The intervention progressed sequentially through a needs-assessment Forum Group Discussion (FGD), a two-day intensive SAK EMKM-focused workshop, and four rounds of direct field mentoring. Effectiveness was measured using a one-group pre-test–post-test design and analyzed with a paired-samples t-test. Findings revealed a highly significant improvement in mean knowledge scores from 42.6 to 79.3 (an 86.2% gain; t = −18.42; p < 0.001; df = 24). At program conclusion, 88% of participants had independently produced SAK EMKM-compliant financial statements encompassing income statements and statements of financial position. Qualitative field observations confirmed a substantive shift from rudimentary cash-book recording toward disciplined double-entry bookkeeping practice. These results affirm the efficacy of structured, phased, practice-centered mentoring as a capacity-building strategy for rural economic entities and offer a transferable model for financial governance improvement across BUMDes in North Sumatra.